The old, weird America : folk themes in Contemporary Art - Duncan, Michael; Kamps, Toby; Sheehy, Colleen; Contemporary Arts Museum Houston, Houston; Frederick R. Weisman Art Museum, Minnesota (Minneapolis) (Houston : Contemporary Arts Museum Houston, 2008)
Beltz, Eric ; Blake, Jeremy ; Durant, Sam ; Furnas, Barnaby ; Grant, Deborah ; Jackson, Matthew Day ; Kahlhamer, Brad ; Kilgallen, Margaret ; McDermott & McGough ; Morse, Aaron ; Norton, Cynthia ; Pratt, Greta ; Rathman, David ; Robleto, Dario ; Smith, Allison ; Walker, Kara ; White, Charlie
Biog., ind. tent., gr. tent., bibliog. p. 145-157
Publication on the occasion of the exhibition 'The old, weird America' at the Contemporary Arts Museum Houston in Houston, 10.05.2008 - 20.07.2008 and at the Frederick R. Weisman Art Museum in Minnesota (Minneapolis), 23.08.2008 - 04.01.2009
boek